Claves para aprender Educación Física durante el confinamiento (Keys to learning Physical Education during confinement) - Del Valle Díaz, Sagrario; Cabanillas Cruz, Esther Cabanillas; Villamil Cabello, Eduardo; de la Vega Marcos, Ricardo (Retos, 2022)
El propósito de este estudio es identificar la relación existente entre el aprendizaje en educación física, la competencia de los docentes y la motivación de los estudiantes durante la cuarentena. Han participado 686 estudiantes de secundaria (297 hombres y 390 mujeres), con diferente clase social y nivel de instrucción, todos ellos proporcionaron datos sobre el conocimiento percibido del aprendizaje en educación física, la motivación intrínseca respecto a sus necesidades psicológicas básicas y la competencia de los profesores. Los datos se analizaron mediante estadística descriptiva y un modelo de regresión múltiple simultánea. Para determinar el mejor predictor de cada subescala del aprendizaje de educación física se examinaron cuatro modelos de mediación paralelos. Los modelos de mediación se realizaron para probar la “mediación simultánea por múltiples variables”. Se encontró que la competencia docente fue un predictor significativo de la transferencia de conocimiento (b = .42, se = .02, p <.001), mediada por necesidades psicológicas competencia, autonomía y relación. El coeficiente de regresión estandarizado fue .42. El efecto indirecto total fue significativo (.17, IC [.13, .21]). Este estudio demuestra que la competencia docente fue un predictor significativo del aprendizaje de la educación física mediado por las necesidades psicológicas básicas de los estudiantes en el confinamiento. Abstract. The purpose of this study was to identify the relationship between learning physical education competence, teachers´ competence and students’ motivation in quarantine. A primary goal of physical education is to develop competence in physically literate individuals with the knowledge, skills, and confidence necessary for a physically active lifestyle. Guided by the teachers´ competence and expectancy-value and interest motivation theories. Method: 686 high school students (297 male and 390 women) from 17 Spanish regions of different social classes and level of instruction, provided data on expectancy beliefs and perceived knowledge of learning competence of physical education, intrinsic motivation, and teachers’ competence. Data were analyzed using descriptive statistics and a simultaneous multiple regression model. To determine the best predictor of each subscale of the learning competence of physical education four parallel mediation models were examined. The mediation models were conducted to test “simultaneous mediation by multiple variables” Results: It was found that teacher competence was a significant predictor of knowledge transference (b = .42, s.e.= .02, p < .001), mediated by psychological needs competence, autonomy, and relatedness. The standardized regression coefficient for this path is .42. The total indirect effect was significant (.17, CI [.13, .21]). Conclusion: This study demonstrates that teacher competence was a significant predictor of learning physical education competence mediated by psychological needs competence. Students’ beliefs about success in physical education have a limited influence on the teachers´ competence and knowing how to attend to the basic psychological needs of the students, in confinement.